2016
DOI: 10.1521/pedi_2015_29_200
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Borderline Personality Disorder Symptoms and Psychosocial Functioning in Adolescence

Abstract: Major gains toward understanding the emergence of borderline personality disorder (BPD) pathology, which is typically first noted during adolescence, have been made. The present study addresses a gap in our understanding of within-person change in BPD symptoms across adolescence and contributes to the limited literature on outcomes associated with adolescent BPD. Using an at-risk community sample of girls (N=2,450), bivariate latent growth curve models were used to analyze the co-development of BPD symptoms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 69 publications
6
43
0
2
Order By: Relevance
“…Third, although the high-risk, community nature of this sample is a strength of the present study, the prevalence of threshold BPD was low. That said, evidence suggests that even subthreshold problems associated with BPD are clinically significant in adolescence, and are associated with poorer social functioning and clinical impairment (Wright et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Third, although the high-risk, community nature of this sample is a strength of the present study, the prevalence of threshold BPD was low. That said, evidence suggests that even subthreshold problems associated with BPD are clinically significant in adolescence, and are associated with poorer social functioning and clinical impairment (Wright et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Given the strong connection between BPD traits and these normal-range personality traits, it is also likely that BPD traits will fail to decline when accompanied by chronic MDD and substance use disorder symptoms; conversely, the remission of comorbid disorders may facilitate a reduction in BPD traits. For instance, a large community sample of adolescent females reported that increasing BPD symptoms were associated with worsening social and mental health outcomes (Wright, Zalewski, Hallquist, Hipwell, & Stepp, 2015). Likewise, adult clinical samples report that the rate of decline in BPD traits is associated with the rate of decline for the personality trait of neuroticism (Wright, Hopwood, & Zanarini, 2015), as well as decline in co-occurring MDD, AUD, and DUD symptoms (De Panfilis et al, 2011; Gunderson et al, 2008; Zanarini et al, 2011; Zanarini Frankenburg, Hennen, Reich, & Silk, 2004).…”
Section: Evidence For Common Cause Predisposition and Pathoplasty Mmentioning
confidence: 99%
“…Given the low base rate of current (i.e., past month) MDD in this sample ( n = 34), as well as evidence of persistent emotional dysfunction among individuals with remitted MDD [41,43,44], we used lifetime MDD diagnoses to categorize participants into High and Low MDD groups. Likewise, given the documented associations of subthreshold BPD (i.e., 3 or 4 BPD criteria) with emotional dysfunction [61] and disability [106], participants endorsing 3 or 4 BPD criteria ( n = 58) were excluded from the present study to reduce overlap between High and Low BPD groups.…”
Section: Studymentioning
confidence: 99%